Modifying the DC Servo Motor Observed by Particle Swarm Optimization Techniques - Saxena, Arti; Panse, Vishal R; Asyhari, Ardian; Umam, Rofiqul; Michalska-Domańska, Marta; Dixit, Aparna (International Journal of Electronics and Communications Systems, 2024)
The PID controller's optimized tuning improves the control system's functionality. This work presented the tuning of the PID/FOPID controller by the conventional Ziegler-Nichols (ZN) method and the Particle Swarm Optimization (PSO) algorithm. The PID controller is the most popular in the industry because it is simple to implement, has good computing ability, and provides a robust system. These methods are implemented on the DC servomotor system to optimize the transient responses like rise time (??), settling time (??), and peak overshoot (??) to get a better result. The PID controller tuned by the conventional ZN method gives a longer settling time, a longer rise time, and a higher peak overshoot. The PSO algorithm is utilized to overcome the significant overshoot and considerable settling time obtained in the conventional Ziegler-Nichols method. Analyzing and comparing the MATLAB simulation results, it is observed that PSO algorithms provide a better-optimized response over the ZN method with FOPID controller in respect of less rise time (?? =0.0392 sec.), less settling time (??=0.0605 sec.) and peak overshoot (??=1.92 percent). The results obtained by the proposed controller provide better reliability and better response.